2023
DOI: 10.3390/ijms241310825
|View full text |Cite
|
Sign up to set email alerts
|

Building a Scaffold for Arteriovenous Fistula Maturation: Unravelling the Role of the Extracellular Matrix

Abstract: Vascular access is the lifeline for patients receiving haemodialysis as kidney replacement therapy. As a surgically created arteriovenous fistula (AVF) provides a high-flow conduit suitable for cannulation, it remains the vascular access of choice. In order to use an AVF successfully, the luminal diameter and the vessel wall of the venous outflow tract have to increase. This process is referred to as AVF maturation. AVF non-maturation is an important limitation of AVFs that contributes to their poor primary pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 166 publications
0
5
0
Order By: Relevance
“…32,33 Due to this complex process, the venous outflow tract or the area near the AVF connection (juxta-anastomotic region) is often responsible for AVF maturation and luminal stenosis, possibly due to thrombosis and the development of intimal hyperplasia in the AVF venous outflow tract. 34,35 Thrombosis plays a minor role in the failure of fistula maturation, and intimal hyperplasia is a more significant mechanism. 36,37 Intimal hyperplasia is an inflammatory process triggered by injury that leads to thickening of the intimal layer, proliferation of vascular smooth muscle cells (VSMCs), and deposition of extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Due to this complex process, the venous outflow tract or the area near the AVF connection (juxta-anastomotic region) is often responsible for AVF maturation and luminal stenosis, possibly due to thrombosis and the development of intimal hyperplasia in the AVF venous outflow tract. 34,35 Thrombosis plays a minor role in the failure of fistula maturation, and intimal hyperplasia is a more significant mechanism. 36,37 Intimal hyperplasia is an inflammatory process triggered by injury that leads to thickening of the intimal layer, proliferation of vascular smooth muscle cells (VSMCs), and deposition of extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…[ 66 ] demonstrated that postoperative venous fibrosis increases universally in patients, and only postoperative venous medial fibrosis determines the stenotic potential of intimal hyperplasia in AVF, ultimately establishing vascular fibrosis as a hallmark of AVF failure. TGF-β assumes a central role in kidney and vascular fibrosis and stands as a determinant for AVF functioning [ 67 ]. Additionally, TGF-β orchestrates inflammation within the remodeling AVF wall [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The successful maturation of a fistula, known as arterialization, hinges on a carefully orchestrated tissue adaptive response, which leads to outward remodeling [7]. The quality and arrangement of the ECM, which governs cellular responses that drive outward-directed proliferation, ensure the requisite thickening of the vein wall without compromising the patency of the venous lumen [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the ECM's quality and integrity in regulating vascular remodeling processes is gaining increasing attention as our understanding of its role in governing vascular adaptation responses expands [4,10]. Substantial efforts have been invested in developing engineered ECM scaffolds that mimic the natural mechanical and biological characteristics of the ECM [11].…”
Section: Introductionmentioning
confidence: 99%